Multiple-land use practices in transfrontier conservation areas: The case of Greater Mapungubwe straddling parts of Botswana, South Africa and Zimbabwe - Sinthumule, Ndidzulafhi Innocent (Bulletin of Geography. Socio-economic Series, 2016)
Transfrontier Conservation Areas (TFCAs) have recently emerged as the 21st century approach to managing protected areas in southern Africa. Unlike national parks and other protected areas that place emphasis only on the protection of plant and animal species within their borders, transfrontier conservation areas promote conservation beyond the borders of protected areas. Consequently, this mega-conservation initiative encourage multiple land-use practices with the purpose of improving rural livelihoods whilst promoting biodiversity conservation. Thus, land parcels under different forms of tenure are brought together into a common nature conservation project. This study argues that the integration of various land-use practices within one area benefits conservation goals at the expense of local communities and irrigation farmers. To substantiate this argument, the study draws on fieldwork material collected in the Greater Mapungubwe Transfrontier Conservation Area spanning parts of Botswana, South Africa and Zimbabwe. The study concludes that multiple-land use practices in transfrontier conservation areas is only promoted by wildlife managers to gain access to extra land.